Couples' Transitions to Parenthood 2016
DOI: 10.4337/9781785366000.00020
|View full text |Cite
|
Sign up to set email alerts
|

The transition to parenthood in Spain: adaptations to ideals

Abstract: The experience of the transition to parenthood in Spain in this edited volume is strongly influenced by the economic crisis, 2008-2014. The vast majority of the couples interviewed for this study spoke about the precariousness of the labour market, job insecurity and not being able to make ends meet on just one paycheck. When the interviewed Spanish parents-to-be added all the leaves they were entitled to-16 weeks of maternity leave, two weeks of paternity leave, two to four weeks of breastfeeding leave and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Romero-Balsas et al (2013) concluded that there is a contrast between fathers who take shorter periods of leave and consider leave a right but not a duty, and more-involved fathers who conceptualize time off as their responsibility and a commitment to their families. Similarly, the TransParent project (Abril et al, 2015; González et al, 2013; González & Jurado-Guerrero, 2015; Seiz et al, 2016) has documented the emergence of a “new fatherhood” in Spain and it classifies fathers as committed, helper , or occasional fathers. Committed fathers hold very egalitarian attitudes, have flexible working conditions, and are less career-oriented than their partners.…”
Section: The Spanish Parental Leave System and Its Usementioning
confidence: 99%
See 1 more Smart Citation
“…Romero-Balsas et al (2013) concluded that there is a contrast between fathers who take shorter periods of leave and consider leave a right but not a duty, and more-involved fathers who conceptualize time off as their responsibility and a commitment to their families. Similarly, the TransParent project (Abril et al, 2015; González et al, 2013; González & Jurado-Guerrero, 2015; Seiz et al, 2016) has documented the emergence of a “new fatherhood” in Spain and it classifies fathers as committed, helper , or occasional fathers. Committed fathers hold very egalitarian attitudes, have flexible working conditions, and are less career-oriented than their partners.…”
Section: The Spanish Parental Leave System and Its Usementioning
confidence: 99%
“…The men in this category—who were approximately equally divided between childless and already a parent—believed that mothers are better caregivers than fathers, and they tended to justify their unequal division of labor by relying on a biological discourse and arguing that since they cannot breastfeed a baby, they are less necessary during early childhood. A detailed approach to this kind of reasoning can be found in Seiz et al (2016). Some men in this group were aware of the uneven division of labor and reported some type of intra-couple conflict.…”
Section: Three Different Part-time Unpaid Parental Leave Use Strategiesmentioning
confidence: 99%
“…Conditions such as being underworked, unable to externalize childcare, or having nonstandard schedules may explain childcare arrangements among spouses to a greater extent than gender attitudes (Deutsch, 1999). With regard to orientation to work, working-class men may be more likely to have an instrumental relationship with their jobs, be somehow “disenchanted” with the labor market, and be more willing to be involved in family activities (Domínguez-Folgueras, Jurado-Guerrero, Botía-Morillas, & Amigot-Leache, 2017b; Seiz et al, 2016). Managers are not only strongly work oriented but also usually integrated in organizational cultures where deviating from traditional masculinity may be more penalized (Abril et al, 2015).…”
Section: Factors That Promote Involved Fatherhood and Shared Childcarementioning
confidence: 99%